Enhanced in vitro and in vivo uptake of a hydrophobic model drug coumarin-6 in the presence of cucurbit[7]uril12. Issue 7 (8th July 2015) - Miao, Xiaoqing; Li, Ye; Wyman, Ian; Lee, Simon M. Y.; Macartney, Donal H.; Zheng, Ying; Wang, Ruibing
<x xml:space="preserve">Abstract</x> Cucurbit[7]uril significantly enhanced in vitro and in vivo uptake of coumarin-6, on an epithelial cell model and a zebrafish model.